Inflammatory Markers, Impulsivity and Aggression in Fibromyalgia Patients - Uslu, Muhammed Fuad; Uslu, Emine Yıldırım; Yildiz, Sevler; Tabara, Muhammed Fatih (My University, 2025)
Background: Fibromyalgia syndrome (FMS) is a chronic pain disorder associated with psychological symptoms, especially impulsivity and aggression. Although inflammation has recently been suggested to play a role in the etiopathogenesis of FMS, the relationship between this mechanism and psychological factors is unclear. The aim of this study was to examine the relationship between inflammatory markers and impulsivity and aggression in FMS patients. Materials and Methods: This study included 73 FMS patients and 73 healthy controls matched for age, gender and body mass index (BMI). Impulsivity was assessed with the Barratt Impulsivity Scale-11 Short Form (BIS-11-SF) and aggression was assessed with the Buss-Perry Aggression Questionnaire (BPAQ). The BIS-11-SF measures mo- tor, cognitive and planning impulsivity, while the BPAQ assesses physical aggression, verbal aggression, anger and hostile attitudes. Neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR), systemic inflammatory response index (SIRI), systemic immune-inflammation index (SII) and aggregate systemic inflammation index (AISI) were analyzed and the relationship between inflammatory markers and psychological parameters was examined with Pearson correlation test. Results: BIS-11-SF (58.6 ± 16.8 vs. 48 ± 15.4, p < 0.001) and BPAQ (71.9 ± 18.4 vs. 55.9 ± 16.8, p < 0.001) scores of FMS patients were significantly higher than the control group. However, no significant difference was found between the groups in terms of NLR, PLR, MLR, SII, SIRI and AISI levels (p > 0.05). In addition, no significant corre- lation was found between inflammatory markers and impulsivity and aggression scores. Conclusions: The high levels of impulsivity and aggression in FMS patients suggest that these psychological factors may play an important role in the symptomatology of the disease. However, the fact that inflammatory markers are not associated with these psychological parameters suggests that hematologic indices may be insufficient to predict impulsivity and aggression. Further studies with larger patient groups may contribute to a more detailed evaluation of these relationships.
Keywords: Fibromyalgia; aggression; inflammatory markers; impulsivity